Droplet spectrum characteristics and drift potential of different droplet classes and spray volumes application of atrazine with nicosulfuron - Neto, Arthur Duarte Rodrigues [UNESP]; Ribeiro, Naiane Antunes Alves [UNESP]; E Oliveira, Fagner Angelo da Silva [UNESP]; Faria, Glaucia Amorim [UNESP]; Prado, Evandro Pereira [UNESP] (FapUNIFESP (SciELO), 2023)
In this research, the Volumetric Median Diameters (VMDs), Relative Span (RS), percentage of droplets with a diameter smaller than 100 µm (V100), and percentage ofdrift (% drift) of four droplet classes (Fine, Medium, Coarse, and Very Coarse) were analyzedin two spray volumes (77 L.ha-1and 144 L.ha-1) employinga tank-mix of atrazine and nicosulfuron herbicides (2500 + 15 gaiha-1), usingParticle/ Droplet Imaging Analyze (PDIA) and wind tunnel techniques. The experiments were performed under Completely Randomized Design, in a 4 × 2 factorial scheme (droplet classes × sprayvolumes). Data underwent analysis of variance and Tukey’s test at 5%, and the correlation between variables was computedconsidering Pearson’s coefficient at 1% and 5%. The VMD of all droplet classes was considerably distinct in the two spray volumes. In both application spray volumes, the minimum VMD for the Coarsedropletclass classification was not attained. The highest means of RS were detectedin the spray volume of 77 L.ha-1. All treatments demonstratedsignificant differences in the analysis of V100 and % drift, with the highest means observed in the Fine droplet (144 L.ha-1) and Medium (77 L.ha-1). A negative correlation existed between VMD × V100 and VMD × % drift and a positive correlation between V100 × % drift in the two spray volumes. RS was negatively correlated with VMD and positively with V100 and % drift, in the spray volume of 77 L.ha-1. In the spray volume of 144 L.ha-1, the correlation between RSand VMD, V100, and % drift was insignificant.
Características do espectro de gotas e potencial de deriva de diferentes classes de gotas e volumes de aplicação da mistura de atrazine com nicosulfuron
Keywords: application technology; droplet size; PDIA; wind tunnel